LOGO AND PACKAGING CREATION FOR SELLING VALUE DEVELOPMENT FOR BREAD, MSME (LIA BAKERY) IN KEDUNG VILLAGE, GUNUNG KALER, TANGERANG - Bahits, Abdul; Kusuma, Aria Cendana; Fatimah, Andini Nur; Antika, Windi; Dewi, Gita Silviana; Abidzar, Muhammad Daffa (Yayasan Education and Social Center, 2024)
This community service activity is aimed at the